Nature Style : Cultivating wellbeing at home with plants - Langan, Alana; Vidal, Jacqui; O'Brien, Annette (Photographer) (Port Melbourne, Victoria : Thomas & Hudson Australia, 2021)
It's no secret that time spent in nature is good for us. Nature helps us thrive, improves our health and wellbeing, decreases stress and increases happiness. But if you don't have the luxury of a forest at your doorstep, bringing the outside in can provide an immediate connection to the natural world and the many benefits that come with it. From the founders of the botanical wares design studio Ivy Muse comes a practical guide to styling the home for health and harmony, using nature as a blueprint. With expert advice on houseplants and how to style them, as well as pro-tips on the choice of decor and materials, finishes and furnishings, this book shows how natural elements can be incorporated into any room in the house - both effectively and affordably. Nature Style is for all those who seek to restore body and mind in a natural and nurturing home environment where houseplants are the heroes.
Plant care
Includes bibliographical references.
Keywords: House plants in interior decoration; House plants in interior decoration -- Psychological aspects; Interior decoration -- Psychological aspects; House plants -- Therapeutic use; Indoor gardening; Nature -- Psychological aspects; Human beings -- Effect of environment on; Herbals